The effects of exercise with nicotine replacement therapy for smoking cessation in adults: A systematic review - Chen, Hui; Yang, Yang; Miyai, Hanna; Yi, Chenju; Oliver, Brian G. (Frontiers in Psychiatry, 2022)
Objective: This systematic review aimed to evaluate the efficacy of exercise programs with nicotine replacement therapy (NRT) for smoking cessation in adults. Introduction: Nicotine addiction is mediated by dopamine. Exercise can also activate the dopamine reward system. Therefore, exercise may effectively facilitate NRT to reduce cigarette cravings and withdrawal symptoms. Inclusion Criteria: Clinical trials between 2000-2022 used exercise protocols of any intensity for smoking cessation, in current smokers or recent quitters of both genders, aged 18-70, without severe diseases and pregnancy. Mental disorders were not excluded, as exercise can improve mental health status. Therefore, it may be as effective among people with mental health issues as the general population in preventing nicotine cravings and supporting abstinence. Methods: Four databases (PubMed, Embase, Cochrane, Medline) were searched for papers in English using the terms' nicotine replacement therapy', 'exercise', and 'smoking cessation'. Titles and abstracts were screened for potentially eligibility before full texts were reviewed. Sample size, gender, study duration, and age was then extracted. The certainty of the evidence was assessed using Joanna Briggs Institute's (JBI's) GRADE approach. Results: Seventeen studies were identified with a total of 3,191 participants. Only one study is not a randomised control study. There was moderate-high quality evidence that exercise can aid NRT in promoting smoking cessation in the short term. Several studies reported temporary reductions in cravings; however, only one trial reported a decrease in cigarette consumption due to exercise intervention and one demonstrated increased smoking abstinence at 1 year of the intervention. Conclusions: Exercise with NRT aids smoking cessation in the short term, but no evidence suggests its efficacy in the long term when combined. Future trials should include larger sample sizes and strategies to increase exercise adherence.